Hiatal hernia with focal megaoesophagus in a Friesian stallion. (17th July 2020) - Lehman, M.; Hendrickson, D.; Selberg, K.
Summary: Hiatal hernia with focal megaoesophagus was diagnosed in a 10‐year‐old Friesian stallion presenting to the referral hospital for further investigation of recurrent oesophageal obstruction. Oesophageal endoscopy revealed dilation of the distal oesophagus with alterations in the mucosa characteristic of gastric mucosa in the distal oesophagus. In addition, a moderate amount of feed material was identified in the distal oesophagus. Positive contrast radiography showed that approximately half of the stomach was herniated cranially through the diaphragm. Management of the disease included recommendations to elevate the patient's torso during feeding and provide mash‐only feeds. Provided that successful control of the megaoesophagus could be achieved, surgical repair of the hiatal hernia may be an option for the future. This is the first report of hiatal herniation in horses. We report the successful conservative management of a stallion with both megaoesophagus and hiatal herniation through elevated feedings and selective exercise management.